HUBUNGAN JENIS MAKANAN DAN INTAKE CAIRAN DENGAN KELELAHAN PADA PEKERJA BAGIAN SETRIKA PT SANDANG ASIA MAJU ABADI - Arumbi, Maria Visca; Kurniawan, Bina; Widjasena, Baju (Jurnal Kesehatan Masyarakat (Undip), 2017)
Fatigue is the body's mechanism to avoid further damage so that the body can recover itself after resting. Fatigue is adjusted centrally by the brain. Work fatigue increases errors in working process and may increase the number of accidents at work. The objective of this study is to describe the correlation between consumed types of diets and fluid intake with fatigue among Ironing Division workers of PT Sandang Asia Maju Abadi. This descriptive study conducted in cross-sectional method in form of observational study. The population studied consists of 37 workers from Ironing Division and sampled by total-sampling method. Instruments used in this study include recall questionnaires of foods and beverages consumed to determine the types of diets and fluid intake, Questemp 34 Heat Stress Monitor to measure the work climate, body weight scale, Microtoise to measure body height, Deary-Liewald Reaction Time to measure the level of work fatigue. The results showed that the respondent consists of 51.4% of young adults, 67.6% of females, and 56.8% of respondent with normal nutritional status, 56.8% of respondents consumes non-gravy-rich diets, and 64.9% of respondents have enough fluid intakes, under work climate ranging between 24 - 36oC. The result of chi-square test shows that there is a correlation between types of diets and fluid intake with fatigue. To reduce the risk of work fatigue, it is recommended for workers to prefer consuming gravy-rich diets and drink enough water to overcome the loss of body fluids.